1998
DOI: 10.1093/ije/27.6.941
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection, garlic intake and precancerous lesions in a Chinese population at low risk of gastric cancer

Abstract: The findings of this study suggest that infection with H. pylori is a risk factor and garlic may be protective, in the development and progression of advanced precancerous gastric lesions in an area of China at relatively low risk of GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 11 publications
5
50
1
Order By: Relevance
“…16) Helicobacter pylori (HP) infection has been linked to stomach cancer and precancerous stomach lesions. [17][18][19] In vitro, garlic extracts have a potent capacity to eliminate HP. 20) We have no information about HP infection in Yangzhong city, but our data from another high-risk area for stomach cancer (Huaian city of Jiangsu province) indicate that frequent intake of raw garlic and Welsh onion may decrease the OR for HP infection (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…16) Helicobacter pylori (HP) infection has been linked to stomach cancer and precancerous stomach lesions. [17][18][19] In vitro, garlic extracts have a potent capacity to eliminate HP. 20) We have no information about HP infection in Yangzhong city, but our data from another high-risk area for stomach cancer (Huaian city of Jiangsu province) indicate that frequent intake of raw garlic and Welsh onion may decrease the OR for HP infection (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The resulted suggested that; increased consumption dose of allium vegetables (e.g. garlic, onion, shallot, etc) would reduce the risk of stomach cancer by 40% [37]. The results had shown that vegetables of allium family can inhibit the tumor growth, H. pylori infections, and vancomycin resistant S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…pylori infection was determined by 13 C-UBT as described previously (28). Briefly, the baseline breath sample was collected from each participant after an overnight fast.…”
Section: C-ubtmentioning
confidence: 99%